Mother’s defense of a juvenile rock squirrel (Otospermophilus variegatus) against a rattlesnake (Crotalus molossus) - González-Jaramillo, Surya Ivonne; Lozano-Amaro, Ileana; Glebskiy, Yury; Cano-Santana, Zenón (Therya Notes, 2023)
Predation of rock squirrels (Otospermophilus variegatus) by rattlesnakes (Crotalus sp.) has led to a coevolutionary process during which rock squirrels have developed resistance to the rattlesnake venom and a series of behaviors that allow squirrels to protect themselves against predation. In this note, we describe an observation of such behavior; how a squirrel mother protects a juvenile against a rattlesnake attack. We witnessed a confrontation between a mother squirrel and a rattlesnake over a juvenile that was attacked by the snake and the squirrel’s strategy used to guide her offspring away from danger. The mother squirrel threatened the rattlesnake by moving its tail and retreated laterally to a nearby tree. The juvenile followed the mother, guided by its smell. When they reached a safe distance, they jumped from the tree and went away, keeping their distance. Before withdrawing, the mother attempted to interact with the observers; local workers confirm that rock squirrels warn them about rattlesnake presence. The defensive behavior we observed was complex and effective. The mother squirrel was able to guide the juvenile out of danger, and the strategy was well planned since they retired to a nearby tree where the rattlesnake would be at a disadvantage. Therefore, rock squirrels have a well-developed behavior to protect their offspring against snake attacks.